Role of Artificial Intelligence in Corporate Training and Development - A Conceptual Paper - Anjali Sabale,; Gomathi S., (International Journal of Intelligent Systems and Applications in Engineering, 2022)
These Human Evolution is one part of Nature. The development in the surroundings increases the value of life and living. We have crossed several ages in this Nature, and Today we are standing in the Information Age. It is the era where knowledge is shared through various valuable sources. Artificial Intelligence is an emerging platform that aims to change the world's technology system. The application of Artificial Intelligence is progressively increasing in Today's world routine life. UNESCO has approved this platform and is in the race to develop and train individuals with Artificial intelligence to change this society into digitalization. Similarly, Artificial Intelligence has dignified its importance on each corporate world stage. Learning the importance of this technology, many firms are incorporating it in full force. Our study emphasizes the importance, impact, and conceptual study of Artificial Intelligence in corporate firms. This research explores the massive opportunities that discover the organization's potential for digital transformation. During this transformation, it is obvious to face numerous challenges and impacts in Business. Therefore, this study will reveal the importance implementing Artificial Intelligence into Training and development process in the organization. Every Business is impacted while in the transformation phase. Similarly, AI is also proven to impact business operations. However, enhancing market leadership and sustainability while implementing AI is challenging.